2022
DOI: 10.3390/ijerph19084890
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Clinical Myelopathy Signs in Smartphone-Using University Students with Neck Pain

Abstract: University students have the highest smartphone-use addiction, which coincides with a rising number in instances of neck pain. As the time in smartphone use increases, neck flexion tends to increase. These positions can affect the spinal cord by the direct and indirect mechanisms which lead to cervical myelopathy. Thus, the current study aimed to determine the prevalence and associated factors of clinical myelopathic signs in smartphone-using university students with neck pain. A total of 237 smartphone-using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…Thus, the increasing proportion of the working-age population who spend most of their time in office environments is also contributing to the increased incidence of NP [ 20 ]. Finally, along with the rise in electronic product use, potential risks for NP have also been reported, which may contribute to the increase in incidence [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the increasing proportion of the working-age population who spend most of their time in office environments is also contributing to the increased incidence of NP [ 20 ]. Finally, along with the rise in electronic product use, potential risks for NP have also been reported, which may contribute to the increase in incidence [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower limit Upper limit Forecast Lower limit Upper limit electronic product use, potential risks for NP have also been reported, which may contribute to the increase in incidence [21].…”
Section: Forecastmentioning
confidence: 99%
“…Each of these clinical tests for myelopathic signs has been compared with magnetic resonance imaging (MRI) results and proven sensitive in detecting cervical myelopathy in the elderly [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Later studies using myelopathic signs categorized adults with neck pain into groups with myelopathic signs present and myelopathic signs absent [ 15 , 16 ]. They concluded that myelopathic signs were associated with adult neck pain, presumably due to either irritation of the spinal cord or temporary spinal cord ischemia [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Later studies using myelopathic signs categorized adults with neck pain into groups with myelopathic signs present and myelopathic signs absent [ 15 , 16 ]. They concluded that myelopathic signs were associated with adult neck pain, presumably due to either irritation of the spinal cord or temporary spinal cord ischemia [ 15 , 16 ]. Thus, in adult patients without myelopathic symptoms (e.g., gait dysfunction, loss of hand dexterity, and motor/sensory dysfunction), the presence of clinical myelopathic signs may be used as the initial evaluation of CSM [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The sample size of the study was 81. It was considered acceptable as described by Naing et al (2006) [ 67 ] and Puntumetakul et al (2022) [ 68 ].…”
Section: Methodsmentioning
confidence: 99%